Brain Natriuretic Peptides in Atherosclerotic Renal Artery Stenosis and Effects of Renal Angioplasty - Elzbieta Nowakowska-Fortuna; Aso Saeed; Gregor Guron; Michael Fu; Ola Hammarsten; Gert Jensen; Hans Herlitz (Karger Publishers, 2013)
Background: We hypothesized that plasma levels of brain natriuretic peptide (BNP) and N-terminal pro-BNP (NT-proBNP) would be elevated, and adiponectin concentrations reduced, in patients with atherosclerotic renal artery stenosis (ARAS) and that BNPs might be used to identify patients who would benefit from percutaneous transluminal renal angioplasty (PTRA). Methods: Data were collected before renal angiography in 91 patients with hypertension and suspected ARAS (significant ARAS; n=47, and non-RAS; n=44) and in 20 healthy controls (C). In ARAS patients analyses were repeated four weeks after PTRA. Results: Ambulatory systolic blood pressure (ASBP) was significantly elevated in the ARAS group vs. both C and non-RAS groups. Baseline plasma BNP and NT-proBNP levels were significantly elevated, and adiponectin concentrations reduced, in the ARAS group vs. C but not vs. the non-RAS group. One month after PTRA, ASBP was reduced vs. baseline (149±16 to 139±15 mm pConclusions: Patients with ARAS showed elevated of BNP and NT-proBNP concentrations, and reduced levels of adiponectin, compared to healthy controls but not vs. hypertensive individuals without RAS. Our data do no support the use of BNP analyses in the identification of ARAS patients who will have a beneficial blood pressure response to PTRA.